MR-TOMOGRAPHY OF THE HEART IN A PATIENT WITH LEFT ATRIUM MYXOMA BEFORE SURGICAL TREATMENT - N. V. Meladze; E. Yu. Strazden; E. E. Vlasova; S. A. Korolev; O. V. Stukalova (Евразийский Кардиологический Журнал, 2020)
Among the large number of benign tumors of the heart myxoma most frequently diagnosed neoplasm intracavitary (occurs in 50%). The clinical picture of a myxoma is extremely various. Often it is diagnosed as a casual find. Usually the diagnosis is established according to an echocardiography. Magnetic resonance imaging is used for inspection of patients with suspicion on myxoma in cases when information of echocardiography is not enough and before surgical treatment. We present clinical follow-up 58 years old patients with left atrial myxoma, which before surgical treatment has executed a heart MRI.